Sertoli cells are the target of environmental toxicants in the testis – a mechanistic and therapeutic insight. (August 2015) - Gao, Ying; Mruk, Dolores D; Cheng, C Yan
<x xml:space="preserve">Abstract</x> Introduction: Sertoli cells support germ cell development in the testis via an elaborate network of cell junctions that confers structural, communicating, and signaling support. However, Sertoli cell junctions and cytoskeletons are the target of environmental toxicants. Because germ cells rely on Sertoli cells for the provision of structural/functional/nutritional support, exposure of males to toxicants leads to germ cell exfoliation due to Sertoli cell injuries. Interestingly, the molecular mechanism(s) by which toxicants induce cytoskeletal disruption that leads to germ cell exfoliation is unclear, until recent years, which are discussed herein. This information can possibly be used to therapeutically manage toxicant-induced infertility/subfertility in human males. Areas covered: In this review, we provide a brief update on the use of Sertoli cell system developed for rodents and humans in vitro, which can be deployed in any research laboratory with minimal upfront setup costs. These systems can be used to collect reliable data applicable to studies in vivo. We also discuss the latest findings on the mechanisms by which toxicants induce Sertoli cell injury, in particular cytoskeletal disruption. We also identify candidate molecules that are likely targets of toxicants. Expert opinion: We provide two hypothetical models delineating the mechanism by which toxicants induce germ cell exfoliation and blood–testis barrier disruption. We also discuss molecules that are the targets of toxicants as therapeutic candidates.